Effects of available soil silicon on the formation of phytoliths in Phragmites australis (Cav.) Trin. ex Streud, Poaceae. Issue 1 (2nd January 2019) - Wang, Jiangyong; Liu, Linjing; Gao, Zhuo; Jie, Dongmei
ABSTRACT: The means by which silicon (Si) influences plant growth has important implications for ecology, nature conservation and biogeochemical cycling of Si. To clarify the effect of available soil silicon content on phytolith formation in plants, we studied phytolith in leaves of Phragmites australis (= Phragmites communis), in correlation with available soil silicon, and available silicon in P. australis from 12 sampling sites in Northeast China. The results showed that available soil silicon content and phytolith concentration in P. australis varied across the sampling sites. The differences of available silicon content in P. australis were great among different growing stages. In July and August, silicon absorbed by plant was mainly used for forming phytolith, resulting in a high phytolith concentration, while phytolith concentration was low in September and October. Phytolith concentration was strongly influenced by the ratio of available silicon content in the soil to that in the plant (S/P). The phytolith concentration was high when S/P was less than about 4, and it was low when S/P was more than about 4. The result of redundancy analysis showed that most phytolith morphotypes in P. australis were negatively correlated with S/P. We conclude that silicon uptake of P. australis gradually changes from active uptake to passive uptake when the available soil silicon content is about four times that in P. australis, and in this concentration range the higher available soil silicon content results in phytolith formation. However, if available soil silicon content is too high, it will inhibit phytolith formation.